2015
DOI: 10.1016/j.carbpol.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effects of superficially deacetylated chitin nanofibrils on the wound healing process

Abstract: Previous reports indicate that the beneficial effect of chitin nanofibrils (CNFs), and chitosan nanofibrils (CSNFs) for wound healing. In this study, the wound healing effects of superficially deacetylated chitin nanofibrils (SDACNFs) were evaluated using an experimental model. In the experiments using circular excision wound model, SDACNFs induced re-epithelium and proliferation of the fibroblasts and collagen tissue. In the chitin, CNFs, and CSNFs, on the other hand, the e-epithelium and proliferation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…Owing to cationic electrostatic repulsive forces, the deacetylated chitin readily disintegrated and the SDACNFs were homogeneously dispersed in water. We have reported that SDACNFs have various biological activities, including effects on obesity and hypercholesterolemia by oral administration [14,15] and on wound healing by topical application [16,17]. In this study, we investigated the prophylactic effects of orally administered SDACNFs against 5-FU-induced intestinal mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to cationic electrostatic repulsive forces, the deacetylated chitin readily disintegrated and the SDACNFs were homogeneously dispersed in water. We have reported that SDACNFs have various biological activities, including effects on obesity and hypercholesterolemia by oral administration [14,15] and on wound healing by topical application [16,17]. In this study, we investigated the prophylactic effects of orally administered SDACNFs against 5-FU-induced intestinal mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…4 When chitin is disintegrated into NF, the hydrophilic surface area increases, enhancing the biochemical significance of the material [13,14]. As disintegrating methods of chitin into NF, ultrasonication, grinding, or the Star Burst system under acidic conditions have been reported [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we isolated chitin nanofibers from crab shells and prepared them using a simple mechanical treatment [2]. Chitin nanofibers have a characteristic morphology [3], high surface-to-volume ratio [4], high mechanical strength [5,6], and efficient biological properties [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%